Analyzing the Content of the Arabic Language Series Book for Teaching Arabic to Non-Native Speakers: A Study in the Context of William Francis Mackey: تحليل محتوى كتاب سلسلة اللغة العربية لتعليم اللغة العربية لغير الناطقين بها: دراسة في سياق وليام فرانسيس ماكي - Asbarin, Asbarin; Wargadinata, Wildana; Rusuly, Usfiyatur; Nailil Amalia, Nabila (Institut Agama Islam Negeri Palangka Raya, 2024)
The aim of this research was to evaluate the compatibility of the content within the book